1H NMR-Based Isolation of Anti-Inflammatory 9,11-Secosteroids from the Octocoral Sinularia leptoclados - Yu-Chia Chang; Kuei-Hung Lai; Sunil Kumar; Po-Jen Chen; Yi-Hsuan Wu; Ching-Long Lai; Hsi-Lung Hsieh; Ping-Jyun Sung; Tsong-Long Hwang (Marine Drugs, 2020)
Octocoral Sinularia leptoclados has been identified as a source of bioactive 9,11-secosteroids. This study adopted a targeted isolation approach to the discovery and analysis of five 9,11-secosteroids, including two novel compounds named sinleptosterols A (1) and B (2) as well as five known analogues (8αH-3β,11-dihydroxy-24-methylene-9,11-secocholest-5-en-9-one (3), 8βH-3β,11-dihydroxy-24-methylene-9,11-secocholest-5-en-9-one (4), leptosterol A (5), (24S)-3β,11-dihydroxy-24-methyl-9,11-secocholest-5-en-9-one (6), and 3β,11-dihydroxy-9,11-secogorgost-5-en-9-one (7)) in terms of 1H-NMR patterns and potency against neutrophilic inflammation. The structure of secosteroids 1 and 2 was deduced from general spectroscopic analysis and an examination of NMR spectra. Among the above-mentioned isolates, compound 4 had the most pronounced effect in inhibiting elastase release and superoxide anion generation, with the IC50 values of 2.96 and 1.63 μM, respectively.